The impact of the use of forecasts in information sets - Giampiero M. Gallo; Clive William John Granger; Yongil Jeon (Deutsche Bank Research, 1999)
We analyze the properties of multiperiod forecasts which are formulated by a number of companies for a fixed horizon ahead which moves each month one period closer and are collected and diffused each month by some polling agency. Some descriptive evidence and a formal model suggest that knowing the viewsexpressed by other forecasters the previous period is influencing individual current forecasts in the form of an attraction to conform to the mean forecast. There are two implications: one is that the forecasts polled in a multiperiod framework cannot be seen as independent from one another and hence the practice of using standard deviations from the forecasts' distribution as if they were standard errors of the estimated mean is not warranted. The second is that the forecasting performance of these groups may be severely affected by the detected imitation behavior and lead to convergence to a value which is not the right target (either the first available figure or some final values available at a later time).
Keywords: C0; C8; C1; 330; multistep forecast; consensus forecast; preliminary data; Prognoseverfahren; Wirtschaftsprognose; Informationswert; Theorie